Interaction effects between possession status and percentage: Insights from modeling match-running performance across possession status in male soccer - Pan, P.; Lago-Peñas, C.; Lorenzo-Martinez, M.; Rein, R.; Liu, T.; Memmert, D.; Serra, R. R.; López Del Campo, R. (Biology of Sport, 2026)
Due to the dynamic and complex nature of soccer, match-running performance (MRP) is highly influenced by match content. This study aimed to examine the interaction between possession status (PS) and possession percentage (PP) in relation to match-running performance (MRP) and to quantify MRP in each PS while considering multiple contextual variables. MRP indicators, including total distance (TD) and high-intensity running distance (HID), were collected from 8,468 observations of 412 outfield male players in the 2018-2019 Spanish LaLiga, excluding matches with red cards. This study set PS, possession percentage (PP), effective playing time, match location, quality of opposition, and match results as fixed effects, and set players and teams as random effects. Results indicated: i) PP interacted with PS, negatively affecting TD (r = -0.26, p < 0.05) and HID (r = -0.11, p < 0.05) during IP but positively influencing TD (r = 0.24, p < 0.05) and HID (r = 0.28, p < 0.05) during OP; ii) MRP during in-possession exceeded out-of-possession when PP was below 36% for TD and 36.4% for HID; iii) PP thresholds for MRP shifts varied by position, with forwards requiring higher PP (TD: 61.8%, HID: 68.6%) compared to central defenders (TD: 28.3%, HID: 9.2%). This study reveals the interaction effects of PS and PP on MRP, emphasizing the complexity of multivariate relationships in soccer. It underscores the importance of multivariate approaches over traditional methods like t-tests, which provide only partial insights.